Shadowing - Lambert, Sylvie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractThis article attempts to bridge the gap between the vocational aspects of simultaneous interpretation and the theoretical and empirical components of simultaneous interpretation by describing the benefits and the versatility of the shadowing technique when used as a pre-simultaneous training tool. Aspects of cognitive psychology and neuropsychological applications are incorporated in a variety of applied exercises.